A new species and new records of Oocyclus Sharp, 1882 (Coleoptera: Hydrophilidae) from Brazil - Jordão, Rafael; Clarkson, Bruno; Ferreira-Jr, Nelson (Zootaxa, 2018)
A new species of Oocyclus Sharp, 1882, O. pilosus sp. nov. is described and illustrated from Mato Grosso State in Central-Western Brazil. Oocyclus itapecum Clarkson & Short 2012 and O. yubai Clarkson & Short 2012 are newly recorded from São Paulo and from Mato Grosso, Goiás and Paraná States respectively. The doubtful record of Oocyclus aeneus Clarkson & Short 2012 in Mato Grosso State is herein confirmed. An updated key to the Brazilian species of Oocyclus is provided.